Changes in ice-shelf buttressing following the collapse of Larsen A Ice Shelf, Antarctica, and the resulting impact on tributaries - Royston, Sam; Gudmundsson, Hilmar (Journal of Glaciology, 2016)
The dominant mass-loss process on the Antarctic Peninsula has been ice-shelf collapse, including the Larsen A Ice Shelf in early 1995. Following this collapse, there was rapid speed up and thinning of its tributary glaciers. We model the impact of this ice-shelf collapse on upstream tributaries, and compare with observations using new datasets of surface velocity and ice thickness. Using a two-horizontal-dimension shallow shelf approximation model, we are able to replicate the observed large increase in surface velocity that occurred within Drygalski Glacier, Antarctic Peninsula. The model results show an instantaneous twofold increase in flux across the grounding line, caused solely from the reduction in backstress through ice shelf removal. This demonstrates the importance of ice-shelf buttressing for flow upstream of the grounding line and highlights the need to explicitly include lateral stresses when modelling real-world settings. We hypothesise that further increases in velocity and flux observed since the ice-shelf collapse result from transient mass redistribution effects. Reproducing these effects poses the next, more stringent test of glacier and ice-sheet modelling studies.